Covid 19 Sebagai Force Majeure untuk Menunda Pelaksanaan Kontrak yang Termuat dalam Akta Notaris: Covid 19 Sebagai Force Majeure untuk Menunda Pelaksanaan Kontrak yang Termuat dalam Akta Notaris - Mahardhika Gilang Aditya (Faculty of Law, University of Jember, Indonesia, 2021)
Corona Virus Disease (Covid 19) has a significant impact on all aspects of human life. One of the aspects affected by Covid 19 is the business sector, especially in contract implementation. A Contract is an agreement made or agreed upon by the parties in writing. An agreement exists because of an act committed between one or more people against one or more people who bind themselves to each other. So that this event creates a legal relationship between the parties, which includes rights and obligations. In a contract, there is usually a clause or arrangement related to a forced condition or what is known as a force majeure (overmacht). The regulation relating to force majeure exists because to protect the debtor when in the execution of the contract contained in the notariil deed, the debtor in carrying out his obligations to the creditor occurs an event that is beyond the power of the party concerned. Force majeure can be categorized as earthquakes, floods, landslides, wars, fires, military coups, embargoes, epidemics, and so on. During the corona pandemic that is currently sweeping all parts of the world certainly has an impact on the implementation of a contract. Therefore, further explanation is needed regarding the impact of Covid 19 as force majeure to delay implementation of the contracts contained in the notarial needed. KEYWORDS: Covid 19, Contract, Force Majeure, Notarial Deed.